Very useful, but do carefully: Mental health researcher views on establishing a Mental Health Expert Consumer Researcher Group. Issue 9 (18th August 2019) - Scholz, Brett; Platania‐Phung, Chris; Gordon, Sarah; Ellis, Pete; Roper, Cath; Bocking, Julia; Happell, Brenda
Accessible summary: What is known on the subject?: Contemporary mental health policy stipulates consumer participation in all aspects of mental health services including service evaluation and other forms of mental health research. Research is identified as underpinning quality mental health services, and therefore, consumers researchers could enhance the mental health sector by contributing to the quality, credibility and relevance of mental health research. What this paper adds to existing knowledge?: Non‐consumer researchers generally supported the concept of a consumer expert reference group for researchers at the individual and institutional level. A consumer expert reference group should reflect diversity and offer expertise relevant to the topic of research and may represent one way to normalize partnerships with consumer researchers and realize the benefits they can bring to research. What are the implications for practice?: Quality mental health services are underpinned by robust research evidence. It is crucial that consumers are active participants in research activity. The availability of a consumer expert reference group could facilitate collaborations between consumer and non‐consumer researchers and contribute to a stronger consumer focus embedded in mental health research. Abstract: Introduction: Contemporary mental health policy identifies consumers as active participants in all aspects of mental health services from design to evaluation. Consumer researchers should be actively involved in mental health research and contribute to quality service delivery. Aim: To gain a snapshot of mental health researcher views on strategies for increasing research by or with consumers in mental health through the establishment of an Expert Consumer Researcher Group (ECRG). Methods: Cross‐sectional survey of 41 non‐consumer mental health researchers from Australia or New Zealand. Results: The introduction of an ECRG was considered an effective strategy for linking consumer and non‐consumer researchers and providing specialist advice on research design and methodology. The most suitable location for this group was identified as within consumer advocacy agencies (71%), universities (66%) or research funding bodies (66%). Participants rated their likelihood of seeking advice from the ECRG as high. Discussion: Research participants supported the value of an ECRG. They emphasized the importance of ensuring the group reflected a diversity of views and offered specialized expertise related to the specific topic. The ECRG could benefit both individual researchers and larger research organizations. Implications for practice: An ECRG could facilitate collaborations with consumer researchers and in turn enhance the quality of mental health research.